PERANAN IBU DALAM MEMPERKENALKAN KONSEP KERAGAMAN AGAMA DAN RAS (SARA) KEPADA ANAK USIA DINI - Chaeroni Chaeroni; Khoirul Anwar (AWLADY : Jurnal Pendidikan Anak, 2018)
Multiculturalism and conflicts caused by SARA in Indonesia have always been a problem that attracts researchers. Many other researchers doing research on this subject, among others by using political, religious, state, and education perspectives. While this study uses another perspective, namely from the perspective of family caring, especially the role of mothers in developing the concept of diversity in childhood as an effort to prevent racial conflict.This research is a qualitative research using a grounded approach. The method used to collect data is interview and focus group discussion (FGD). This research was conducted in two sub-districts, namely Gayamsari and Genuk sub-districts.The results of this study indicate that the shift in family parenting patterns has reduced the intensity of communication between parents and children. This shift causes parents to "loose hands" and give up full teaching on the values of diversity and differences in schools. Does the house remain a place where learning practices of diversity are happening? This turned out to be no longer an awareness for parents. The parents tend to be "passive" ie not teaching about diversity unless it is asked by their children. In fact, understanding how families instill diversity values intensely from an early age becomes important for this multicultural nation.